The cooling tower water microbiota: Seasonal dynamics and co-occurrence of bacterial and protist phylotypes - Tsao, Han-Fei; Scheikl, Ute; Herbold, Craig; Indra, Alexander; Walochnik, Julia; Horn, Matthias (Water research (Oxford), 2019)
Cooling towers for heating, ventilation and air conditioning are ubiquitous in the built environment. Often located on rooftops, their semi-open water basins provide a suitable environment for microbial growth. They are recognized as a potential source of bacterial pathogens and have been associated with disease outbreaks such as Legionnaires’ disease. While measures to minimize public health risks are in place, the general microbial and protist community structure and dynamics in these systems remain largely elusive. In this study, we analysed the microbiome of the bulk water from the basins of three cooling towers by 16S and 18S rRNA gene amplicon sequencing over the course of one year. Bacterial diversity in all three towers was broadly comparable to other freshwater systems, yet less diverse than natural environments; the most abundant taxa are also frequently found in freshwater or drinking water. While each cooling tower had a pronounced site-specific microbial community, taxa shared among all locations mainly included groups generally associated with biofilm formation. We also detected several groups related to known opportunistic pathogens, such as Legionella, Mycobacterium, and Pseudomonas species, albeit at generally low abundance. Although cooling towers represent a rather stable environment, microbial community composition was highly dynamic and subject to seasonal change. Protists are important members of the cooling tower water microbiome and known reservoirs for bacterial pathogens. Co-occurrence analysis of bacteria and protist taxa successfully captured known interactions between amoeba-associated bacteria and their hosts, and predicted a large number of additional relationships involving ciliates and other protists. Together, this study provides an unbiased and comprehensive overview of microbial diversity of cooling tower water basins, establishing a framework for investigating and assessing public health risks associated with these man-made freshwater environments. [Display omitted] •Highly dynamic bacterial and protist community structure in cooling towers.•Cooling tower water basin communities resemble other open freshwater environments.•Core bacterial microbiome of cooling towers consists of biofilm-forming taxa.•Co-occurrence network analysis suggests importance of inter-kingdom relationships.